Jural relations of middle-class marriage and women as legal subjects in the imaginary of ‘new India’ - Grover, Shalini (The Australian journal of anthropology, 2017)
In India's capital New Delhi, four Family Courts were set up between 2009 and 2012, and 12 mediation institutions known as Crime Against Women Cells (CAW cells) were established during the same period. The Indian state has also endorsed gender-equalising family legislation, mutual-consent divorce and introduced new language of and for mediation. Together with India's projection of a rising global economy, these recent legal changes have engendered perceptions of a dramatic upturn in formal divorce and of women as liberal legal subjects. In the anthropology of Asia, marital practices have crucially informed our comprehension of modernisation, family formations and moral panics. This article explores the impact of new forms of legal availability on marriage, family and kinship among the metropolitan middle classes. It ethnographically engages with important structural shifts reflected in the intimate lives of Hindu couples, but also foregrounds a cautious narrative of newly imagined jural relations.